Customized Incubation Services and Growth of Tenants: The Mediating Effect of Behavior Orientation of Social Networking Services - Zhang, Li; Zhou, Yongtao (Frontiers in Psychology, 2021)
The third-generation incubator is generally characterized by embedment of social networking and customized incubation services are closely embedded in the social networking. How the social networking play their role in the process that customized incubation services facilitate the growth of tenant? In order to disclose whether social networking services (SNS) mediate the impact of customized incubation services on the growth of tenants, this article focuses on the whole process where customized services facilitate the growth of tenants by means of social networking services. First, it employs situational theory and contingency theory to analysis why customized services result in behavior of social networking services; second, it explores why behavior of social networking services facilitates the growth of tenants based on co-production theory and social network theory; next, it conduct a study on the direct relationship between customized services and growth of tenants anchoring on the theory of co-production, customer satisfaction, and dynamic environment. Based on these theories, it develops the overall theoretical model of mediating effect. Following that, it conducts empirical test: it has first ascertained whether there is a positive relationship between customized services and growth of tenants. Then, three paths of the theoretical model have been measured by means of the structural model. At the same time, the t-test and the Sobel test are employed to justify their significance. If we only contemplate customized incubation services and growth of tenants, they are positively correlative. On the other hand, if referring to the role of social networking services in this process, we disclosed that not only customized incubation services positively impact behavior of social networking services, but also behavior of social networking services positively facilitates the growth of tenants; at the same time, the customized incubation services exhibit no direct impact on the growth of tenants otherwise. It witnesses that the behavior of social networking services fully mediates the relationship between customized services and the growth of tenants. As a result, we should promote incubation services to be deeply embedded in social networking services; incubator management should even improve the capability to deal with big data embedded in social networking services. In additional, entrepreneurial ecosystems should be also embedded in social networks intensively.